Third-Party Responsibility Against Cooperative Legal Action - Hariyanto, Hariyanto; Fadlan Sejati, Herlambang; Iyer, Puneet (Faculty of Law, Universitas Negeri Semarang, 2023)
This research is a theoretical study of the third-party responsibility concept against cooperative legal actions based on Law Number 25 of 1992. This is normative legal research. Data analysis obtained from library research was carried out in a qualitative way. The data obtained were grouped systematically and then linked to the formulation of the existing problems based on their accuracy value in order to get a clear picture of the discussion. Results showed that the positive law regarding cooperatives gave the board of directors the right to appoint a manager who came from a third party outside the cooperative. The board of directors and managers are bound by employment agreements. The board of directors remains fully responsible for legal actions committed by managers in cooperative management.